2019
DOI: 10.1021/acs.jpcc.9b07603
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Look on the Nature of Dual-Band Emission of Octahedral Copper-Iodide Clusters—Promising Ratiometric Luminescent Thermometers

Abstract: For the first time, the 3(X + M)­LCT origin of both the lowest excited triplet states of dual-emissive tetranuclear copper­(I)-iodide complexes with the octahedral Cu4I4 core has been revealed using quantum chemical computations in contrast to the conventional assignment of the lowest-energy emission to the 3CC state. The unusual thermochromic behavior shown for dual emission from these states of Cu4I4 clusters stabilized by P,N-ligands allows optical ratiometric thermal sensing in a broad temperature range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 76 publications
2
26
0
Order By: Relevance
“…20c and d is an octahedral Cu 4 I 4 cluster ( 23) recently reported by Kolesnikov and coworkers. 117 It showed dual emissions which were both considered to be of 3 (X + M)LCT character. Interestingly, with an increase of the temperature from −175 to 125°C, both emissions at 505 and 621 nm were thermally quenched albeit with different degrees of quenching.…”
Section: Organic-inorganic Hybrid Clustersmentioning
confidence: 99%
“…20c and d is an octahedral Cu 4 I 4 cluster ( 23) recently reported by Kolesnikov and coworkers. 117 It showed dual emissions which were both considered to be of 3 (X + M)LCT character. Interestingly, with an increase of the temperature from −175 to 125°C, both emissions at 505 and 621 nm were thermally quenched albeit with different degrees of quenching.…”
Section: Organic-inorganic Hybrid Clustersmentioning
confidence: 99%
“…It is difficult to generalize the parameters related to molecular thermometers, since while a system may excel in some respects it may be lacking in others. Molecular thermometers have been created using organic fluorescence dyes or transition metal complexes or clusters [3, 6, 8–12] . However, such systems have drawbacks since they usually exhibit limited photostability that depends on the intensity and duration of the light exposure, and can suffer from fluorescence intensity changes that are not related to variations of temperature but to modifications of pH, solvent viscosity or polarity, biological environment, or ionic strength.…”
Section: Figurementioning
confidence: 99%
“…Molecular thermometers have been created using organic fluorescence dyes or transition metal complexes or clusters. [3,6,[8][9][10][11][12] However, such systems have drawbacks since they usually exhibit limited photostability that depends on the intensity and duration of the light exposure, and can suffer from fluorescence intensity changes that are not related to variationso f temperature butt om odificationso fp H, solvent viscosity or polarity,b iological environment, or ionic strength.T he wide emissionb andwidths of organic reporters can complicate the interpretations of resultsi np ractical applications, and moreover,t he luminescence lifetimes are most often used in the evaluation of temperature in such systems, with inherent drawbacks such as longera cquisition times and the requirement of rigorous post-processing data treatment as well as the inadequacy in mapping temperature gradients. [5] Lanthanide-basedn anothermometers [13] may derive their functionality from the temperature-dependent luminescence of lanthanide cations (Ln 3 + )i nt heir compounds.…”
mentioning
confidence: 99%
“…[13] At the same time, analogous tetranuclearc lusters have been reported,w hich are formally built up by combining two Cu 2 I 2 subunits. [10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] At this point, it is important to mention that the very first OLED based on Cu I contained the tetranuclear complexC u 4 (CCph) 4 L 2 (L = 1,8-bis(diphenylphosphino)-3,6-dioxaoctane). [29] Lu et al reported on ah ighly luminescent tetranuclear system with aC u 4 Cl 4 core and 2-(bis(2-methyl-phenyl)phosphino)-6-methylpyridine as bridging ligand,s howinga combination of TADF and fast phosphorescence at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, analogous tetranuclear clusters have been reported, which are formally built up by combining two Cu 2 I 2 subunits [10, 14–28] . At this point, it is important to mention that the very first OLED based on Cu I contained the tetranuclear complex Cu 4 (C≡ Cph ) 4 L 2 (L = 1,8‐bis(diphenylphosphino)‐3,6‐dioxaoctane) [29] .…”
Section: Introductionmentioning
confidence: 99%